Tính \(\cos\alpha;tan\alpha;\cot\alpha\)
biết \(\sin\alpha=\frac{5}{13}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1) \(cot\alpha=\sqrt[]{5}\Rightarrow tan\alpha=\dfrac{1}{\sqrt[]{5}}\)
\(C=sin^2\alpha-sin\alpha.cos\alpha+cos^2\alpha\)
\(\Leftrightarrow C=\dfrac{1}{cos^2\alpha}\left(tan^2\alpha-tan\alpha+1\right)\)
\(\Leftrightarrow C=\left(1+tan^2\alpha\right)\left(tan^2\alpha-tan\alpha+1\right)\)
\(\Leftrightarrow C=\left(1+\dfrac{1}{5}\right)\left(\dfrac{1}{5}-\dfrac{1}{\sqrt[]{5}}+1\right)\)
\(\Leftrightarrow C=\dfrac{6}{5}\left(\dfrac{6}{5}-\dfrac{\sqrt[]{5}}{5}\right)=\dfrac{6}{25}\left(6-\sqrt[]{5}\right)\)
1: \(cota=\sqrt{5}\)
=>\(cosa=\sqrt{5}\cdot sina\)
\(1+cot^2a=\dfrac{1}{sin^2a}\)
=>\(\dfrac{1}{sin^2a}=1+5=6\)
=>\(sin^2a=\dfrac{1}{6}\)
\(C=sin^2a-sina\cdot\sqrt{5}\cdot sina+\left(\sqrt{5}\cdot sina\right)^2\)
\(=sin^2a\left(1-\sqrt{5}+5\right)=\dfrac{1}{6}\cdot\left(6-\sqrt{5}\right)\)
2: tan a=3
=>sin a=3*cosa
\(1+tan^2a=\dfrac{1}{cos^2a}\)
=>\(\dfrac{1}{cos^2a}=1+9=10\)
=>\(cos^2a=\dfrac{1}{10}\)
\(B=\dfrac{3\cdot cosa-cosa}{27\cdot cos^3a+3\cdot cos^3a+2\cdot3\cdot cosa}\)
\(=\dfrac{2\cdot cosa}{30cos^3a+6cosa}=\dfrac{2}{30cos^2a+6}\)
\(=\dfrac{2}{3+6}=\dfrac{2}{9}\)
Lời giải:
\(M=\frac{\frac{\sin a}{\cos a}+1}{\frac{\sin a}{\cos a}-1}=\frac{\tan a+1}{\tan a-1}=\frac{\frac{3}{5}+1}{\frac{3}{5}-1}=-4\)
\(N = \frac{\frac{\sin a\cos a}{\cos ^2a}}{\frac{\sin ^2a-\cos ^2a}{\cos ^2a}}=\frac{\frac{\sin a}{\cos a}}{(\frac{\sin a}{\cos a})^2-1}=\frac{\tan a}{\tan ^2a-1}=\frac{\frac{3}{5}}{\frac{3^2}{5^2}-1}=\frac{-15}{16}\)
\(\dfrac{sina+cosa}{sina-cosa}=\dfrac{\dfrac{sina+cosa}{cosa}}{\dfrac{sina-cosa}{cosa}}=\dfrac{tana+1}{tana-1}=\dfrac{3}{1}=3\)
Có \(\dfrac{sin\alpha}{cos\alpha}=tan\alpha=2\)\(\Rightarrow sin\alpha=2cos\alpha\)
\(\dfrac{sin\alpha+cos\alpha}{sin\alpha-cos\alpha}=\dfrac{2cos\alpha+cos\alpha}{2cos\alpha-cos\alpha}=\dfrac{3cos\alpha}{cos\alpha}=3\)
a) \(\dfrac{2sina+3cosa}{3sina-4cosa}=\dfrac{9}{5}\)
b) \(\dfrac{sina.cosa}{sin^2a-sina.cosa+cos^2a}=0\)
\(a.\dfrac{2\sin\alpha+3\cos\alpha}{3\sin\alpha-4\cos\alpha}=\dfrac{2\left(3cos\alpha\right)+3cos\alpha}{3\left(3cos\alpha\right)-4cos\alpha}=\dfrac{9cos\alpha}{5cos\alpha}=\dfrac{9}{5}\)
\(b.\dfrac{sin\alpha cos\alpha}{sin^2\alpha-sin\alpha cos\alpha+cos^2\alpha}=\dfrac{3cos^2\alpha}{9cos^2\alpha-3cos^2\alpha+cos^2\alpha}=\dfrac{3cos^2\alpha}{7cos^2\alpha}=\dfrac{3}{7}\)
E = sin^6 + cos^6 + 3sin^2.cos^2
= (sin^2 + cos^2)(sin^4 - sin^2.cos^2 + cos^4) + 3 sin^2.cos^2
= (sin^2 + cos^2)^2 - 3sin^2.cos^2 + 3sin^2.cos^2
= 1
Ta có :
\(\begin{array}{l}B = \cos \frac{{3\alpha }}{2}.\cos \frac{\alpha }{2} = \frac{1}{2}\left[ {\cos \left( {\frac{{3\alpha }}{2} + \frac{\alpha }{2}} \right) + \cos \left( {\frac{{3\alpha }}{2} - \frac{\alpha }{2}} \right)} \right]\\ = \frac{1}{2}\left[ {\cos (2\alpha ) + \cos \alpha } \right] = \frac{1}{2}\left[ {2.{{\cos }^2}\alpha - 1 + \cos \alpha } \right] = \frac{1}{2}\left[ {2.{{\left( {\frac{2}{3}} \right)}^2} - 1 + \frac{2}{3}} \right] = \frac{5}{{18}}\end{array}\)
\(90< a< 180\)
=>\(sina>0;cosa< 0\)
mà cosa=2/3
nên đề sai rồi bạn
\(\sin\alpha=\frac{5}{13}\) => \(\sin^2\alpha=\frac{25}{169}\)
Mà \(\cos^2\alpha+\sin^2\alpha=1\) nên \(\cos^2\alpha=\frac{144}{169}\) => \(\cos\alpha=\frac{12}{13}\)
Ta có \(\tan\alpha=\frac{\sin\alpha}{\cos\alpha}\) => \(\tan\alpha=\frac{5}{13}:\frac{12}{13}=\frac{5}{12}\)
Lại có \(\cot\alpha=\frac{\cos\alpha}{\sin\alpha}\) => \(\cot\alpha=\frac{12}{13}:\frac{5}{13}=\frac{12}{5}\)
Chúc bạn làm bài tốt
Ta có \(\sin^2\alpha+\cos^2\alpha=1\)
\(\Rightarrow\cos^2\alpha=1-\sin^2\alpha\)
\(\Rightarrow\cos^2\alpha=1-\frac{25}{169}=\frac{144}{169}\Rightarrow\cos\alpha=\frac{12}{13}\)
Ta lại có \(\tan\alpha=\frac{\sin\alpha}{\cos\alpha}=\frac{5}{13}.\frac{13}{12}=\frac{5}{12}\Rightarrow\cot\alpha=\frac{12}{5}\)